The Effect of Cephalic Arch Stenosis Location on Angioplasty Success and Patency at 3 and 6 Months in Patients with Brachiocephalic Fistula - Peri Handayani; Patrianef Patrianef; Wawan Mulyawan (Eduvest - Journal of Universal Studies, 2026)
Failure of maturation and stenosis are major obstacles to arteriovenous fistula patency in hemodialysis patients. The cephalic arch commonly develops vascular dysfunction and can be divided into four domains. However, no study in Indonesia has evaluated the effect of cephalic arch stenosis location on angioplasty outcomes. This study aimed to determine the relationship between the location of cephalic arch stenosis and angioplasty success, as well as 3- and 6-month patency in patients with brachiocephalic fistulas, and to identify influencing factors. This retrospective cohort study included 68 patients with cephalic arch stenosis and brachiocephalic fistulas treated in outpatient clinics or inpatient wards at Cipto Mangunkusumo Hospital (RSCM) from January 2022 to December 2024. Data were obtained from medical records. Bivariate analysis was performed using the Chi-square or Fisher’s exact test, and multivariate analysis was conducted using Firth logistic regression. The angioplasty success rate was 91.2%, with 3-month patency of 87.1% and 6-month patency of 66.7%. Multivariate analysis showed that stent use was significantly associated with reduced 3-month patency after angioplasty (OR 0.12; 95% CI 0.02–0.93; p = 0.042), and a cephalic arch insertion angle ≥60° was associated with decreased 6-month patency after angioplasty (OR 0.23; 95% CI 0.06–0.77; p = 0.017). Stenosis location, age, sex, degree and length of stenosis, cephalic arch insertion angle, number of balloons, balloon size, balloon pressure, balloon type, stent use, hypertension, and diabetes were not associated with residual stenosis or with 3- and 6-month patency after angioplasty.